2003
DOI: 10.1139/w03-059
|View full text |Cite
|
Sign up to set email alerts
|

The infection process of Colletotrichum graminicola and relative aggressiveness on four turfgrass species

Abstract: Detached 3-week-old leaves of Agrostis palustris, Lolium perenne, Poa annua, and Poa pratensis were inoculated with conidial suspensions of two isolates of Colletotrichum graminicola obtained from A. palustris. Inoculated leaves were incubated at 23 degrees C under high relative humidity (>95%). The infection process was investigated by light microscopy from 2 to 168 h after inoculation (AI). Spore germination was observed within 2 h AI, appressoria within 6 h AI, and penetration pores within 8 h AI on all fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
1
21
0
3
Order By: Relevance
“…Latunde-Dada et al, (1996) reported acervuli sporulation in C. destructivum-cowpea pathosystem 120 hai. On C. graminicola-Agrostis palustris and C. graminicola-Lolium perenne pathosystems the acervuli sporulation appeared within 72 and 96 hai, respectively (Khan and Hsiang, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Latunde-Dada et al, (1996) reported acervuli sporulation in C. destructivum-cowpea pathosystem 120 hai. On C. graminicola-Agrostis palustris and C. graminicola-Lolium perenne pathosystems the acervuli sporulation appeared within 72 and 96 hai, respectively (Khan and Hsiang, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Half of each section was directly mounted onto glass slide in a water droplet, covered with a cover slip and observed under light and GFP filters. Sections were subsequently stained with lactophenol cotton blue to verify the presence of the hyphae [31]. The other half was placed on PDA and incubated at 24 °C with 12 h photoperiod for 3 days to further validate the presence of the fungus.…”
Section: Pathogenicity Testing Of Transformants and Microscopymentioning
confidence: 99%
“…Members of the genus Colletotrichum are known as cosmopolitan plant pathogens (Sreenivasaprasad and Talhinhas 2005), many of which cause anthracnose in several commercially important crops (Byrne et al 1997; Lardner et al 1999; Khan and Hsiang 2003; Horowitz et al 2004; Xiao et al 2004). Literature on the phytopathogenic genus Colletotrichum (Bailey and Jeger 1992; Prusky et al 2000) includes a single report of the species C .…”
Section: Introductionmentioning
confidence: 99%